Comparison of marker models for the analysis of the volume variation and thoracoabdominal motion pattern in untrained and trained participants - Levai, K.; Dickinson, J.; Winter, S.; Schena, E.; Silvestri, S. (Journal of Biomechanics, 2018)
Respiratory assessment and the biomechanical analysis of chest and abdomen motion during breathing can be carried out using motion capture systems. An advantage of this methodology is that it allows analysis of compartmental breathing volumes, thoraco-abdominal patterns, percentage contribution of each compartment and the coordination between compartments. In the literature, mainly, two marker models are reported, a full marker model of 89 markers placed on the trunk and a reduced marker model with 32 markers. However, in practice, positioning and post-process a large number of markers on the trunk can be time-consuming. In this study, the full marker model was compared against the one that uses a reduced number of markers, in order to evaluate (i) their capability to obtain respiratory parameters (breath-by-breath tidal volumes) and thoracoabdominal motion pattern (compartmental percentage contributions, and coordination between compartments) during quiet breathing, and (ii) their response in different groups such as trained and untrained, male and female.